Respuesta :

Answer:

3 x 2 − 2 x + 4 = 2 x 2 − 4

Step-by-step explanation:

Write the problem as a mathematical expression.

3 x 2 − 2 x + 4 = 2 x 2 − 4

Subtract  2 x 2 − 4  from both sides of the equation.

3 x 2 − 2 x + 4 − 2 x 2 − 4 = 0

Simplify each term.

Subtract  4  from  2 . 3 x 2 − 2 x + 4 − 2 x − 2 = 0

Rewrite the expression using the negative exponent rule  

b − n =1 b n . 3 x 2 − 2 x + 4 − 2 1 x 2 = 0

Combine  − 2  and  1 x 2 . 3 x 2 − 2 x + 4 + − 2 x 2 = 0

Move the negative in front of the fraction.

3 x 2 − 2 x + 4 − 2 x 2 = 0

ACCESS MORE